﻿Multiplicités surréalistes - Cummins, Louis (RACAR : Revue d'art canadienne / Canadian Art Review, 1991)
Selecting Meret Oppenheim’s Fur-Covered Cup, Saucer and Spoon (1936) as the paradigmatic surrealist object, this article tries to show how the critical reception of the work has generally overlooked the actual disrupting functions of surrealist objects at both their psychological and epistemological levels. Furthermore relying on Roland Barthes’s text “The Semantics of the Object” which analyzes the dual—metaphorical and metonymical—character of objects, this article suggests that the increasing fascination for hybrid things in Surrealists’ activities during the 1930s not only offers the opportunity for a symbolic interpretation, but also requires a contextual reading of their typical presentation in exhibitions. It is only at these levels that the amplitude of the Surrealists’ epistemological project as some sort of Borghesian heterotopical taxonomy can be fully understood. Finally, the gendering of Meret Oppenheim’s piece opens up a criticism of the Freudian theory on fetishism, usually conceived as an essentially masculine perversion towards the sexually neutralized theory developed in Mélanie Klein’s analysis of pre-Oedipian part-objects. This assumption can be supported by the Surrealists’ texts on the paranoid function of the objects they had the urge to make.